Synthesis, characterization and toxicity of intercalated zinc- layered material for nanodelivery of salicylate as an anti-inflammatory agent - Ramli, Munirah (2013)
The existing organic based-vectors employed for delivery of therapeutic molecules into cells suffer from a number of setbacks ranging from delivery efficiency to severe toxicity. Through fabrication of novel nano-sized inorganic delivery vectors, problems associated with cellular delivery systems are gradually being addressed. The use of layered materials as carriers of a multitude of therapeutic compounds has garnered much interest, particularly due to their ease of synthesis, rich functionality and good biocompatibility. This study sought to develop a new organic-inorganic nanohybrids based on layered double hydroxides (LDH) and zinc layered hydroxides (ZLH) which contains an anti-inflammatory agent, salicylate (SA) and to test the effect of these nanohybrids on viability of cells. The co-precipitation route was utilized for synthesis of Zn/Al LDH containing SA while direct reaction of aqueous SA with commercial zinc oxide was used for synthesis of ZLH-SA nanohybrids. Intercalation of SA into LDH and ZLH was confirmed by expansions of the basal spacing recorded in the powder X-ray diffraction analysis (PXRD). The basal spacing for SA-LDH nanohybrid was 15.34 Å, with the SA anions orientated as a tilted bilayer. In SA-ZLH nanohybrid, intercalation resulted in a basal spacing of 15.73 Å, with the SA anions arranged as a monolayer at an angle of 57°. Fourier transform infrared (FTIR) spectra revealed the presence of functional groups characteristic of both the host (LDH/ZLH) and SA in the synthesized nanohybrids. Occupation of SA into LDH and ZLH intergallery was further supported by the CHNS data, in which the anion loading percentage was calculated to be 27.75 % for the former and 29.66 % for the latter. The resulting nanohybrids were further characterized using inductively coupled plasma-atomic emission spectroscopy (ICP-AES), thermogravimetric analyzer, analysis of surface area and porosity (ASAP) and field emission scanning electron microscopy (FESEM). Methyltriazoltetrazolium (MTT) assay showed that Zn/Al LDH-SA nanohybrids were less toxic than its LDH, with an IC50 value of 0.737 mg/ml for the former and 0.420 mg/ml for the latter. On the contrary, ZLH-SA nanohybrids (IC50 = 0.052 mg/ml) were more toxic than the free zinc oxide (IC50 = 0.942mg/ml). Based on these findings, it was concluded that LDH show an immense potential to be further developed into alternative cellular delivery vectors while ZLH requires an extensive research in order to better ascertain its application in a drug delivery system.